EKSPERIMENTASI PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN PENDEKATAN OPEN-ENDED PADA POKOK BAHASAN LOGARITMA DITINJAU DARI GAYA BERPIKIR DAN KREATIVITAS PESERTA DIDIK KELAS X SMA NEGERI SE-KABUPATEN GUNUNG KIDUL TAHUN PELAJARAN 2012/2013 - Mella Yuliani (Jurnal Pembelajaran Matematika, 2013)
Abstract:The aim of the research was to determine and comparecooperative learning model of the STAD type with the open-ended approach and STAD viewed from the thinking style and the creativity of toward learners student mathematics learning achievement.This research used the quasi-experimental research method with the factorial design of 2 x 2 x 2. Its population was all of the students in Grade X of State Senior Secondary Schools in Gunungkidul in Academic Year 2012/2013.Based on the results of the data analyses, the conclusions were as follows. 1) The cooperative learning model of the STAD type with the open-ended resulted in a better learning achievement than the STAD type. 2) The students with the sequential thinking style have a better learning achievement than those with the random thinking style. 3) The students with the high creativity have a better learning achievement than those with the low creativity. 4)(a) In the sequential thinking style, the students treated to the cooperative learning model of the STAD type with the open-ended approach have the same learning achievement as those treated with the STAD type; and (b) In the random thinking style, students treated to the cooperativelearning model of the STAD type with the open-ended approach have a better learning achievement than those treated with the STAD type. 5)(a) in the high creativity, the cooperative learning model of the STAD type with the open-ended approach results in a better learning achievement than that of the STAD type; and (b) in the low creativity, the cooperative learning model of the STAD type with the open-ended approach results in the same learning achievement as that of the STAD type. 6) (a) In the high creativity, the students with the sequential thinking style have a better learning achievement than those with the random thinking style; (b) In the low creativity, the students with the sequential thinking style have the same learning achievement as those with the random thinking style; (c) in the sequential thinking style, the students with the high creativity have a better learning achievement than those with the low creativity; and (d) In the random thinking style, the students with the high creativity have the same learning achievement as those with the low creativity. 7) In the sequential thinking style with the high creativity and the low creativity and in the random thinking style with the low creativity, the cooperative learning model of the STAD type with the open-ended approach results in the same learning achievement as that of the STAD type,and in the random thinking style with the high creativity, the cooperative learning model of the STAD type with theopen-ended approach results in a better learning achievement than thatof the STAD type.Keywords: Learning achievement in Mathematics, STAD, open-ended, thinking style, and creativity.